A new stall delay algorithm for predicting the aerodynamics loads on wind turbine blades for axial and yawed conditions. Issue 9 (29th May 2017) - Elgammi, Moutaz; Sant, Tonio
Abstract: Stall delay is a complicated phenomenon that has gained for many years the attention of industry and academics in the fields of helicopter and wind turbine aerodynamics. Since most of the potential flow theories still rely on the use of 2D aerofoil data for simulating loads on a rotating blade, less degree of accuracy is expected because of 3D rotational effects. In this work, a new model for correcting the 2D steady aerodynamic data for 3D effects is presented. The model can reduce the uncertainty in the blade design process and, subsequently, make wind turbines more cost‐effective. This model combines the stall delay model of Corrigan and Schillings, a modified version of an inviscid stall delay model, a new modification factor to account for the effect of the angle of attack changes and a new tip loss factor. Furthermore, the model applies the use of the separation factor of Du and Selig to evaluate the area on the rotor disc where stall delay is most prominent. The new stall delay model was embedded in a free‐wake vortex model to estimate the aerodynamic loads on the National Renewable Energy Laboratory Phase VI rotor blades consisting of the S809 aerofoil sections. The results in this study confirm the validity of the 3D corrections by the proposed new model under both axial and yawed flow conditions. Copyright © 2017 John Wiley & Sons, Ltd.